Analyzing the root causes of neurosurgery complaints: a case study of 5 complaints - Bahram Aminmansour; Hamed Shoaee; Vahid Moghtader; Niloufar Talebi Meimand; Donya Sheibani Tehrani (Interdisciplinary Neurosurgery, 2025)
Introduction: By the end of 2022, the amount of medical malpractice has increased by 11.8% compared to the previous year, of which 46.6% have resulted in a conviction. Considering the importance of this issue, the present study aimed to determine the frequency of medical errors in the field of neurosurgery during the last five years. Method: The present study was a cross-sectional descriptive study. The statistical population included 5 cases of patient complaints against neurosurgeons, which were analyzed. Results: The results of this study showed that communication between doctor and patient is an inseparable part of the process of reducing complaints from doctors. Conclusion: Based on the results of this study, it is suggested that the attending physician should provide clear justification to the patients, and more attention should be paid to the issue of communication between the physician and the patient.